MEDIATING THE INTERESTS: THE STUDY OF THE COUNCIL OF ‘ULAMA’ INDONESIA OF BANTEN PROVINCE'S ROLES ON THE DISCOURSE OF THE IMPLEMENTATION OF SYARI’AH IN BANTEN - Rohman Rohman (Al Qalam, 2011)
After the ruin o the New Order era in 1998, the struggle to implement syarrah in Indonesia came into a new historical phase. During this period, several Radical Islamic movements were established both as a respond to the collapse of the New Order regime which trammels their activities and as a respond to several horizontal conflicts triggered by religious issues which were frequently occurred the fall of the Suharto's regime. In the pipe line, the discourse of the implementation of Islamic syari'ah occurred not only in national level, but also in local level. The Banten province established in 2000 was one of the important regions in the map of Islamic movements in fighting out the implementation of Islamic syariah. In this regard, the Majelis Ulama Indonesia of Banten province played a great role, especially in mediating various interests involved in this discourse fight in local level Even though Muslims failed in bringing the regional regulations into realiry to make Banten Province as Aceh which has implemented Islamic syari'ah, the emergence of several local regulations in several municipalities shows that this discourse is still alive up to the present